Light Intensity Meter and Rear Position Lamp Height: Addition to Indonesian Road Safety Regulations - T, Satrio Dafid B.; Aprianto, Rizal; Ridwan, Asep (RSF Conference Series: Engineering and Technology, 2022)
Forty-six percent of traffic accidents in Indonesia occur on the toll road, and 86 percent of road accidents are due to human error. The number of accidents on the toll road involving heavy vehicles is 33 percent, with the cause of the accident being hit by a vehicle from behind. This incident was caused by the driver's loss of visual perception of the presence of the vehicle in front of him, namely the driver was unable to estimate its existence with the distance of the vehicle in front, one of the reasons was that the driver did not clearly see the light emitted by the vehicle in front of him. Vehicle inspection to the vehicle class must be tested, necessary to do, which is to find out whether the vehicle is suitable for operation or not. Indonesia has not set rules that limit the light intensity and height of rear-light vehicles. From these problems, research was conducted on the design of measuring devices for measuring light intensity and height of the rear light for road safety regulations in Indonesia. The Research and Development (R&D) method is used in this study. This research is a development of previous research in designing a measuring device. Based on the design, manufacture, and testing results, this device can function according to the program design. The device design has been tested and validated, and it is hoped it can be in government policy and be applied to Vehicle Inspection Stations (UPUBKB) throughout Indonesia.